LEGAL HARMONIZATION OF MEDICAL CANNABIS REGULATION IN THE FULFILLMENT OF THE RIGHT TO HEALTH IN INDONESIA - Darojat, Rafan; Brouwer, Darryl Evan; Yuanitasari, Deviana (Universitas Padjadjaran, 2025)
Indonesia’s prohibition of cannabis originates from its adherence to international narcotics conventions, which historically denied recognition of cannabis’s medical value. However, the reclassification of cannabis by the Commission on Narcotic Drugs (CND) in 2020 marked a significant shift in the global legal paradigm by acknowledging its therapeutic potential. This study examines the problem of legal inconsistency between Indonesia’s strict prohibition policy and the development of international standards regarding medical cannabis. This research employs a conceptual legal approach to analyze developments in international narcotics policy and their relevance to Indonesia’s narcotics law. The findings demonstrate that Indonesia’s current legal framework, particularly Law Number 35 of 2009 and Minister of Health Regulation Number 30 of 2023, creates legal disharmony with international developments and restricts the fulfillment of the right to health. From a humanistic perspective, this condition also affects patients who require alternative medical treatment, thereby raising concerns regarding equitable access to healthcare services. This study concludes that Indonesia should adjust its legal framework by permitting the limited use of cannabis for medical purposes under strict regulation. Such reform is consistent with the mandate of Constitutional Court Decision Number 106/PUU-XVIII/2020, which emphasizes the importance of opening legal space for research on medical cannabis.